2010
DOI: 10.5558/tfc86709-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the social bases of satisfaction with public participation in forest management decision-making in British Columbia

Abstract: This study draws upon the results of a survey of the general public in three communities in British Columbia to examine the social bases of satisfaction with public participation in forest management decision-making at both the local and provincial levels. The main findings are that those members of the general public who are relatively more biocentrically oriented (as indicated by the NEP Scale) are less satisfied, and those who have acquaintanceship ties to people employed in the forestry sector are more sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…These results are in line with previous studies evaluating public priorities for forest management in BC, which generally find a preference for environmental values over social and economic values [12,45]. Our study also highlights the high importance of procedural objectives, indicating that stakeholders and Indigenous Peoples are as concerned about the fairness, effectiveness, and inclusiveness of the decision-making process as they are about its outcomes [49,50]. Perhaps the most important result lies in the finding that mitigating climate change, while perceived as important, is not considered as the highest priority, but as just one of many objectives that should be considered when developing forest carbon management strategies.…”
Section: Final Aggregated List Of Objectives and Their Relative Imporsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with previous studies evaluating public priorities for forest management in BC, which generally find a preference for environmental values over social and economic values [12,45]. Our study also highlights the high importance of procedural objectives, indicating that stakeholders and Indigenous Peoples are as concerned about the fairness, effectiveness, and inclusiveness of the decision-making process as they are about its outcomes [49,50]. Perhaps the most important result lies in the finding that mitigating climate change, while perceived as important, is not considered as the highest priority, but as just one of many objectives that should be considered when developing forest carbon management strategies.…”
Section: Final Aggregated List Of Objectives and Their Relative Imporsupporting
confidence: 91%
“…Interestingly, procedural objectives are less frequently highlighted by these studies, even though the category appears in many well-known lists of criteria and indicators, often under a category referring to policy, legal, and/or institutional issues [46][47][48]. Other studies, by analysing public participation in forest management, specifically focus on procedural objectives [49]. For analysis purposes, the 11-point continuous linguistic scale used for the group evaluation of the mitigation strategies was transformed into numeric scores.…”
Section: Final Aggregated List Of Objectives and Their Relative Impormentioning
confidence: 99%
“…This effect may relate to perceived scientific uncertainty; research and monitoring would enable ongoing improvements in implementation and quicker detection of unexpected and problematic impacts, which may otherwise go unnoticed. Respondents also reported high levels of public trust in scientists and low public trust in government and industry in the BC context (Tindall et al 2010, Peterson St-Laurent et al 2019. AM may, therefore, be more acceptable when scientists are perceived to inform policy and management decisions.…”
Section: Type Of Informationmentioning
confidence: 99%
“…A recent review of the literature [31] found that the first publication mentioning the application of participatory planning to FMDSS was presented in the 1990s. Examining current trends in FMDSS, participatory planning is the most recent addition into the conceptual framework of FMDSS [13,14,32,33].…”
Section: Lessons Learned On the Construction And Use Of Fmdssmentioning
confidence: 99%